2018
DOI: 10.18280/ijht.360102
|View full text |Cite
|
Sign up to set email alerts
|

Specific features of heat exchangers calculation considering the laminar boundary layer, the transitional and turbulent thermal conductivity of heat carriers

Abstract: The sources of the literature are analyzed in the article on the influence of the average thickness of the laminar boundary layer (LBL) on the heat transfer coefficient of the various heat-conducting systems. Different authors at different times established the explicit correlation dependence of the increase in heat transfer coefficients with a decrease in the average thickness of the LBL. The average thickness of the LBL according to the literature data was reduced in the various ways (using electric or magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(35 citation statements)
references
References 20 publications
0
24
0
8
Order By: Relevance
“…Based on our works [29][30][31][32][33][34], we concluded that our proposed model of contacting metal surfaces with regard to their the binding energy and surface energy [29][30][31], as well as consideration of the movement of heat-transfer fluids near the metal walls of the heat exchange equipment with taking into account surface forces [32][33][34], has the right to exist. Based on this, we set ourselves the following tasks in this work:…”
Section: Problem Formulationmentioning
confidence: 90%
See 4 more Smart Citations
“…Based on our works [29][30][31][32][33][34], we concluded that our proposed model of contacting metal surfaces with regard to their the binding energy and surface energy [29][30][31], as well as consideration of the movement of heat-transfer fluids near the metal walls of the heat exchange equipment with taking into account surface forces [32][33][34], has the right to exist. Based on this, we set ourselves the following tasks in this work:…”
Section: Problem Formulationmentioning
confidence: 90%
“…At the same time, the value 0 1 P CK  reflects the speed of thermal movement at the molecular level, having the dimension m/s, and the value V is the linear speed of movement of the coolant with the nanoparticles at T mode. We also remind that the transitional viscosity of a fluid, the value of which we derived in previous works [33,34], is the viscosity at the interface of LBL and turbulent flow, having dimension (Pa.s) and calculated by formula 3, and dimensionless turbulent number is the ratio of turbulent to transition viscosity (4) In addition, the dimensionless number Bl is (5) [33,34].…”
Section: Analysis Of the Forces Acting On The Nanoparticle Based On mentioning
confidence: 98%
See 3 more Smart Citations